2015
DOI: 10.1093/mnras/stv2804
|View full text |Cite
|
Sign up to set email alerts
|

Testing the isotropy of the Universe by using the JLA compilation of Type Ia supernovae

Abstract: We probe the possible anisotropy of the Universe by using the JLA compilation of type-Ia supernovae. We apply the Markov Chain Monte Carlo (MCMC) method to constrain the amplitude and direction of anisotropy in three cosmological models. For the dipole-modulated ΛCDM model, the anisotropic amplitude is consistent with zero at 68% C.L., and has an upper bound A D < 1.98 × 10 −3 at 95% C.L. Regardless of much larger uncertainty, we find the dipole direction of JLA is amazingly opposite to that of Union2. Similar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 57 publications
(72 reference statements)
2
71
0
Order By: Relevance
“…A similar cosmic anisotropy has been found in the Union2.1 sample (Yang et al 2014;Javanmardi et al 2015;Bengaly et al 2015;Li et al 2015;Lin et al 2016b). Different with the Union2 or Union2.1 sample, the JLA sample doesn't show any convincing evidence for the existence of the cosmic anisotropy (Bengaly et al 2015;Lin et al 2016a;Chang et al 2018a;Wang & Wang 2018;Deng & Wei 2018b;Sun & Wang 2018a). Constraining the anisotropic amplitude and direction in ΛCDM, ωCDM and CPL models with the JLA sample gave a zero result (Lin et al 2016a).…”
Section: Introductionmentioning
confidence: 51%
“…A similar cosmic anisotropy has been found in the Union2.1 sample (Yang et al 2014;Javanmardi et al 2015;Bengaly et al 2015;Li et al 2015;Lin et al 2016b). Different with the Union2 or Union2.1 sample, the JLA sample doesn't show any convincing evidence for the existence of the cosmic anisotropy (Bengaly et al 2015;Lin et al 2016a;Chang et al 2018a;Wang & Wang 2018;Deng & Wei 2018b;Sun & Wang 2018a). Constraining the anisotropic amplitude and direction in ΛCDM, ωCDM and CPL models with the JLA sample gave a zero result (Lin et al 2016a).…”
Section: Introductionmentioning
confidence: 51%
“…The dipole direction points * https://github.com/dscolnic/Pantheon † https://emcee.readthedocs.io/en/stable/ ‡ We use the highest posterior density (HPD) credible interval method to determine the 68% CL. Model At the end, we make some comparisons between the dipole directions mentioned above in the Pantheon sample with that derived from the Union2 sample [39], Union2.1 sample [44] and JLA sample [50]. The dipole directions in each SNe Ia sample are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [55] used the JLA sample to constrain the anisotropic universe model with Bianchi-I metric and found the model was consistent with the isotropic universe. Constraining the anisotropic amplitude and direction in three different cosmological models of dark energy with the JLA sample gave a zero result [50]. Sang et al [57] performed a tomographic analysis on the JLA sample taking account of redshift dependence of SNe Ia color-luminosity parameter β in the dipole-modulated ΛCDM model, but they did not find any significant deviation from the isotropic universe.…”
Section: Introductionmentioning
confidence: 99%
“…There are several evidences for this hypotheses. The recent analysis [35] showed that the dipole directions of two different Sne Ia data sets, Union 2 [36] and JLA [37], are inconsistent. The dipole directions of Union2 derived using two different methods are almost opposite [38].…”
Section: Discussionmentioning
confidence: 99%